EKSEKUSI KAPAL MOTOR AKIBAT WANPRESTASI PEMBIAYAAN MUSYARAKAH DI PENGADILAN AGAMA GRESIK PERSPEKTIF HUKUM EKONOMI SYARIAH (Analisis Penetapan Eksekusi Pa.Gresik Nomor : 005/Pdt.G/Eks/2017/Pa.Gs.) - alfarihah, Atiqotul maula; Hadi, Abd (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
ABSTRACT                                                      Thesis entitled "Execution of Motorboats as a Result of Musharaka Financing Failure in Religious Court of Gresik in the Perspective of Islamic Economic Law“ (Analysis of the Execution Establishment in the Religious Court of Gresik Number : 005/Pdt.G/Eks/2017/PA.Gs.) is deliberated by the presence of an Execution that is carried out in the Religious Court of Gresik based on the Mortgage Deed Grosse Number : 572/2013 on November 7th, 2013 that hold an oath with the sentence "For Justice Based On Belief In The One and Only God" which was released by the Ministry of Directorate General of Sea Transportation, Batam Port Office, in the form of mortgage level I Debt Repayment with the cost of Rp.27.500.000.000,- .The research method used in this research is field research that has qualitative traits, which resourced from research informant that was collected while doing the research in the Religious Court of Gresik and was supported with a data that could be enhanced with literatures as an upholder. This research is qualitative descriptive, using interview, observation, and documentation data collecting technique. The approaching method used on this research is sosiological juridical which kater analyzed using inductive mindset.Based on the analysis result and related researches on Execution of Motorboats as a Result of Musharaka Financing Failure in Religious Court of Gresik in the Perspective of Islamic Economic Law, analysis of the Execution Establishment in the Religious Court of Gresik Number : 005/Pdt.G/Eks/2017/PA.Gs., evaluating based on Constitutional Law Number 3, Year of 2006 about the modification upon Constitutional Law Number 7, Year of 1989 about Religious Court, Constitutional Law Number 50, Year of 2009 about the second modification upon Constitutional Law Number 7, Year of 1989 about Religious Court, Supreme Court Law Number 2, Year of 2008 about Islamic Economic Laws Compilation, Constitutional Law Number 21, Year of 2008 about Islamic Banking and the Statute Book of Trading Laws, it can be concluded that the execution implementation based on islamic economic laws in Indonesia is under the authority of the Religious Courts. And the execution implementation in the Religious Court of Gresik with the basis of Mortgage Deed Grosse is already in accordance with the Islamic Economic Dispute Laws and the Constitutional Laws.Keywords : Execution, Financing Failure, Musharaka, Islamic Economic Law, Religious Court of Gresik